2020
DOI: 10.1088/1361-6463/ab7139
|View full text |Cite
|
Sign up to set email alerts
|

Ionic wind produced by a DC needle-to-plate corona discharge with a gap of 15 mm

Abstract: The goal of the present study is to better understand the electrohydrodynamic (EHD) phenomena occurring in 15 mm gap point-to-plate corona discharges supplied by positive and negative DC voltages, and to link them to the discharge regime. For that, discharge current measurements have been conducted and a 20 kHz Particle Image Velocimetry system has been used to characterize the ionic wind produced by the discharges. The main results are as follows: (a) the Townsend’s law can always correctly interpolate the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…It can be observed that it increases firstly logarithmically with frequency (up to about 100 Hz, 300 Hz and 500 Hz for the square, sinus and triangle waveforms, respectively), and then, the slope suddenly increases. The last remark is general: the power consumption is comparable in amplitude to the power consumed by DC coronas 27 , as it is weak and limited to about 1 W.
Figure 2 Electrical power consumption versus voltage amplitude V AC for f AC = 200 Hz ( a ) and electrical power consumption versus frequency f AC for V AC = 12 kV ( b ).
…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…It can be observed that it increases firstly logarithmically with frequency (up to about 100 Hz, 300 Hz and 500 Hz for the square, sinus and triangle waveforms, respectively), and then, the slope suddenly increases. The last remark is general: the power consumption is comparable in amplitude to the power consumed by DC coronas 27 , as it is weak and limited to about 1 W.
Figure 2 Electrical power consumption versus voltage amplitude V AC for f AC = 200 Hz ( a ) and electrical power consumption versus frequency f AC for V AC = 12 kV ( b ).
…”
Section: Resultsmentioning
confidence: 93%
“…This is highlighted by high current pulses with magnitudes reaching about 6 mA here and a frequency varying between 5 and 7 kHz (in the case of the sine high voltage). On the other hand, one can observe that the negative corona discharge results in more numerous current pulses but weaker in magnitude, each of them corresponding to a Trichel pulse, as in negative DC coronas 27 . When focusing on these Trichel pulses, one can see that their amplitude is limited to about 0.2 mA with a frequency between 100 and 400 kHz, depending on the v AC (t) value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations